History, geography and civics : teaching and learning in the primary years - Buchanan, John, 1959- (Cambridge University Press, 2013)
History, Geography and Civics provides an in-depth and engaging introduction to teaching and learning socio-environmental education from F-6 in Australia and New Zealand. It explores the centrality of socio-environmental issues to all aspects of life and education and makes explicit links between pedagogical theories and classroom activities. Part I introduces readers to teaching and learning history, geography and environmental studies, and civics and citizenship, as well as issues in intercultural and global education. Part II explores the use of media and sources, values and attitudes, assessment and creative teaching. Each chapter provides links to the Australian Curriculum, including cross-curriculum priorities: sustainability, Aboriginal and Torres Strait Islander education, and Asia and Australia's engagement with Asia. History, Geography and Civics encourages the reader to consider their own beliefs, values and attitudes in relation to their teaching and includes provocations and reflective questions to foster discussion and engagement.